The Ultra-Long Study: A Randomized Controlled Trial Evaluating Long-Term GnRH Downregulation Prior to ART in Women With Endometriosis. Issue 1 (January 2022) - Tomassetti, C.; Beukeleirs, T.; Conforti, A.; Debrock, S.; Peeraer, K.; Meuleman, C.; D'Hooghe, T.
Abstract : (Abstracted from Hum Reprod 2021;36:2676–2686) Although the adverse effect of endometriosis on pregnancy rate is well established, the impact of endometriosis on pregnancy rate after treatment with assisted reproductive technology (ART) remains unclear. There is evidence that the use of prolonged pituitary downregulation before ART in women with any degree of endometriosis increases the odds of clinical pregnancy significantly (up to 4-fold); however, this evidence is limited by potential methodology and publication bias.